The Republics of the Southern Caucasus on their way to the ‘Socialist federation’ (1917–1922) - L. S. Gatagova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2022)
As we approach the 100th anniversary of the formation of the USSR, political, military, social, ethnic and other determinants of consolidation of the peoples and territories of the former Russian Empire within the Bolshevik state attract an increasing interest of academic community. In particular, special attention is drawn to the complex and controversial process of integration of the South Caucasus with Soviet Russia. Soviet historiography advanced an official view on the role of the Transcaucasian republics in the formation of the USSR, which came down to a number of ideological clichés that provided an impoverished and partly distorted image of this complex phenomenon. On the basis of a wide range of Soviet, Russian, and foreign researches, as well as recently published primary sources, the author examines the landmark events in the history of the states of the South Caucasus in the period preceding the formation of the USSR. The author highlights both similarities and differences in the views of Soviet and modern historians on the related issues, including the realization of the right to self-determination of the peoples of the South Caucasus in the first years after the October Revolution and the complex impact of international political situation on the regional developments. The author notes that the struggle for spheres of influence between world powers also affected all the Transcaucasian republics, although with different results. The author pays special attention to the process of Sovietization: in the Soviet historiography it was portrayed as a triumphal march of Soviet rule, but, as recent researches has shown, the Bolsheviks actually did not have a clear and consistent plan for the Sovietization of the Transcaucasian republics and the process was accompanied by dramatic events and conflicts. The assessments of the subsequent formation of the Transcaucasian Federation also differ significantly. The Soviet interpretation of this project emphasized its importance for eliminating the consequences of the Civil War and resolving inter-ethnic conflicts. Contemporary historians point to the fact that the unification process was imposed artificially, and even forcefully, according to some assessments, by Moscow, and its unifying effect was rather mixed. In this context, the author emphasizes the need for an impartial and balanced research approach towards the processes that took place in the Transcaucasian republics in the first post-revolutionary years in order to gain a better understanding of their role in the creation of the USSR.